Derivation of ZF6HP26 Speed Transmission - Zsila, Klaudia; Tiba, Zsolt (International Journal of Engineering and Management Sciences, 2022)
Due to the increasing importance of automation, automatic transmissions have appeared. The different ratios of the transmission may be achieved by braking and coupling the corresponding elements of the planetary gear sets connected in series. The focus of the study is on the ZF6HP26 transmission. After disassembly and clarifying the teeth number of the gears, we derived the equations parametricly providing the ratios using the speed equations published in the literature. The ratio of each gear is calculated by substituting the particular teeth numbers into the derived equations.